Development of tracer relations and chemical ozone loss during the setup phase of the polar vortex - Tilmes, Simone (author); Mueller, Rolf (author); Grooss, Jens-Uwe (author); Nakajima, H. (author); Sasano, Y. (author) (Journal of Geophysical Research, 2006)
The development of tracer-tracer relations in the polar stratosphere is analyzed during the period when the vortex forms and a westerly circulation develops after polar summer (the setup phase of the polar vortex). We consider high southern latitudes from March to June for winter 1997 and 2003 and high northern latitudes from September to October 2003. ILAS and ILAS-II satellite observations and model simulations are used to investigate chemical changes in O₃, NO₂ and HNO₃ during these periods. Tracer-tracer relations and meteorological analyses consistently indicate a separation of the incipient polar vortex into two parts. The area within the edge of the inner vortex is isolated from the outer part that is still influenced by mixing with air of midlatitude origin. In the Antarctic in April, ozone concentrations vary by about 0.5 ppmv within the isolated inner vortex between 500 and 600 K potential temperature. This inhomogeneous distribution of ozone is likewise obvious in MIPAS satellite measurements. Box model simulations explain that the low ozone concentrations in April are caused by chemical ozone loss due to catalytic cycles which are mainly driven by NO x at this time of the year. The simulations also explain the observed conversion of NO x to HNO₃ during the setup phase of the 2003 Antarctic vortex. During June in the Antarctic, the internal vortex transport barrier disappears and ozone mixing ratios become homogeneous throughout the entire vortex. At that time, no further ozone loss occurs because of the lack of sunlight.